2022
DOI: 10.1371/journal.pntd.0010258
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-linked chemotherapy with a low dose of benznidazole plus a bivalent recombinant protein vaccine prevents the development of cardiac fibrosis caused by Trypanosoma cruzi in chronically-infected BALB/c mice

Abstract: Background Chagas disease (CD) is caused by Trypanosoma cruzi and affects 6–7 million people worldwide. Approximately 30% of chronic patients develop chronic chagasic cardiomyopathy (CCC) after decades. Benznidazole (BNZ), one of the first-line chemotherapy used for CD, induces toxicity and fails to halt the progression of CCC in chronic patients. The recombinant parasite-derived antigens, including Tc24, Tc24-C4, TSA-1, and TSA-1-C4 with Toll-like receptor 4 (TLR-4) agonist-adjuvants reduce cardiac parasite b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…This indicates opportunities for clinical dose-reduction of BNZ when implemented as part of a combination treatment regimen, which may help lessen treatment adverse effects 5569 . In combination with our timecourse findings and prior work by us and colleagues 31,33,[70][71][72] , these results demonstrate that successful CD treatment will necessitate not only parasite clearance, but also the lessening of host tissue dysfunction, and may indicate a need to redefine the CD target product profile for therapeutics and for assessment of treatment efficacy [27][28][29]73,74 . Our metabolomic approach also provides a method to test new interventions for their superiority to BNZ-only treatment prior to clinical implementation, as demonstrated here with BNZ+Tc24-C4/E6020-SE vaccine combination treatment.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This indicates opportunities for clinical dose-reduction of BNZ when implemented as part of a combination treatment regimen, which may help lessen treatment adverse effects 5569 . In combination with our timecourse findings and prior work by us and colleagues 31,33,[70][71][72] , these results demonstrate that successful CD treatment will necessitate not only parasite clearance, but also the lessening of host tissue dysfunction, and may indicate a need to redefine the CD target product profile for therapeutics and for assessment of treatment efficacy [27][28][29]73,74 . Our metabolomic approach also provides a method to test new interventions for their superiority to BNZ-only treatment prior to clinical implementation, as demonstrated here with BNZ+Tc24-C4/E6020-SE vaccine combination treatment.…”
Section: Discussionsupporting
confidence: 76%
“…When used as an immunotherapy in experimentally infected mice, the vaccine increased levels of antigen-specific CD8 + cells as well as the key cytokines IFNγ, IL-10, and IL-17A 24,27,28 . Importantly, combining this vaccine with BNZ treatment in a vaccine-linked chemotherapy strategy led to significantly reduced cardiac pathology while reducing the amount of BNZ necessary for efficacy [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Prochetto et al showed that vaccination with three doses of a recombinant Trans-sialidase protein combined with ISPA adjuvant, followed by a curative course of BNZ led to reduced cardiac arrhythmias and fibrosis in chronically infected mice (Prochetto et al, 2022). Dzul-Huchim et al observed significantly reduced cardiac fibrosis in chronically infected mice that were vaccinated with two doses of a vaccine containing both recombinant TSA-1 protein and Tc24-C4 protein combined with E6020 SE adjuvant concurrently with a 7 day course of low dose BNZ treatment (Dzul-Huchim et al, 2022). Altogether, these data provide proof-of-concept that combining BNZ with vaccines can effectively targeting both the parasite and the deleterious host immune responses and improve cardiac function.…”
Section: Therapeutic Vaccination Significantly Reduced Cardiac Pathologymentioning
confidence: 99%
“…Further, the vaccine induced a balanced T H 1/T H 2/T H 17 immune response ( Cruz-Chan et al., 2021 ). More recently, vaccine-linked chemotherapy strategies using recombinant trans-sialidase protein (TSA-1) alone, or TSA1-C4 combined with Tc24-C4 protein, have been tested in mouse models of chronic infection and shown to also reduce tissue pathology ( Dzul-Huchim et al., 2022 ; Prochetto et al., 2022 ). What we had not yet tested and proved was whether our vaccine-linked chemotherapy strategy improved cardiac function during chronic T. cruzi infection.…”
Section: Introductionmentioning
confidence: 99%
“…With Dr. Peter Hotez at Baylor College of Medicine, we have generated a bivalent vaccine against T. cruzi , and preliminary data seem promising in the Baylor murine model of Chagas disease. 29 Clinical development of this vaccine seems warranted, particularly since the vector is spreading north into the southern United States.…”
Section: Novel Cardiovascular Mrna Therapies In Developmentmentioning
confidence: 99%